The distribution of progenitor cells in the subependymal layer of the lateral ventricle in the normal and Huntington’s disease human brain - Curtis, M.A.; Penney, E.B.; Pearson, J.; Dragunow, M.; Connor, B.; Faull, R.L.M. (Neuroscience, 2005)
The recent demonstration of endogenous stem/progenitor cells in the adult mammalian brain raises the exciting possibility that these undifferentiated cells may be able to generate new neurons for cell replacement in neurodegenerative diseases such as Huntington’s disease (HD). Previous studies have shown that neural stem cells in the rodent brain subependymal layer (SEL), adjacent to the caudate nucleus, proliferate and differentiate into neurons and glial cells and that neurogenesis occurs in the hippocampus and the SEL of the caudate nucleus in the adult human brain, but no previous study has shown the extent to which progenitor cells are found in the SEL in the normal and diseased human brain with respect to location. From detailed serial section studies we have shown that overall, there is a 2.7-fold increase in the number of proliferating cell nuclear antigen positive cells in HD (grade 2/3); most notably, the ventral and central regions of the SEL adjacent to the caudate nucleus contained the highest number of proliferating cells and in all areas and regions examined there were more cells in the HD SEL compared with the normal brain. Furthermore, progenitor cells colocalized with βIII tubulin in a subset of cells in the SEL indicating neurogenesis in the HD brain. There was a 2.6-fold increase in the number of new neurons that were produced in the Huntington’s disease SEL compared with the normal SEL; however, the Huntington’s disease SEL had many more proliferating progenitor cells; thus, the proportion of new neuron production relative to the number of progenitor cells was approximately the same. This study provides new evidence of the pattern of neurogenesis in the normal and HD brain.